A preliminary investigation into differences in hops' aroma attributes. (1st November 2017) - Barry, Susan; Muggah, Elizabeth M.; McSweeney, Matthew B.; Walker, Shane
Summary: Consumers are welcoming the use of locally sourced ingredients in their beer, and hops are now beginning to be grown in new regions. One new region is the province of Nova Scotia, Canada. Four different hop varieties (Cascade, Mt. Hood, Golding and Nugget) were sourced from Nova Scotia, and matching varieties (Cascade, Mt. Hood and Nugget) were sourced from Oregon, USA, and England, UK. The main objective of this study was to identify whether differences in the hop aroma exist based on their geographic origin. Projective mapping trials ( n = 2) were conducted for the aroma of all eight hops varieties. The first trial utilised crushed whole‐leaf hops, while the second consisted of a dry‐hopped conventional Canadian lager. Results indicated that there are differences in the hop aromas of both whole‐leaf hops and dry‐hopped lager. Abstract : Four varieties of hops were sourced from Nova Scotia, Canada. The aroma attributes of these hops were compared to hops grown in other geographic regions using projective mapping. Results indicated that there are differences in the hop aromas of whole leaf hops and dry hopped lager.